89.7k views
4 votes
Factor the folowing equation completely and be sure to show all work: x⁴-10x²+4.​

1 Answer

6 votes

x4-10x2+9=0

Four solutions were found :

x = 3

x = -3

x = 1

x = -1

Step by step solution :

Step 1 :

Equation at the end of step 1 :

((x4) - (2•5x2)) + 9 = 0

Step 2 :

Trying to factor by splitting the middle term

2.1 Factoring x4-10x2+9

The first term is, x4 its coefficient is 1 .

The middle term is, -10x2 its coefficient is -10 .

The last term, "the constant", is +9

Step-1 : Multiply the coefficient of the first term by the constant 1 • 9 = 9

Step-2 : Find two factors of 9 whose sum equals the coefficient of the middle term, which is -10 .

-9 + -1 = -10 That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -9 and -1

x4 - 9x2 - 1x2 - 9

Step-4 : Add up the first 2 terms, pulling out like factors :

x2 • (x2-9)

Add up the last 2 terms, pulling out common factors :

1 • (x2-9)

Step-5 : Add up the four terms of step 4 :

(x2-1) • (x2-9)

Which is the desired factorization

Trying to factor as a Difference of Squares :

2.2 Factoring: x2-1

Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)

Proof : (A+B) • (A-B) =

A2 - AB + BA - B2 =

A2 - AB + AB - B2 =

A2 - B2

Note : AB = BA is the commutative property of multiplication.

Note : - AB + AB equals zero and is therefore eliminated from the expression.

Check : 1 is the square of 1

Check : x2 is the square of x1

Factorization is : (x + 1) • (x - 1)

Trying to factor as a Difference of Squares :

2.3 Factoring: x2 - 9

Check : 9 is the square of 3

Check : x2 is the square of x1

Factorization is : (x + 3) • (x - 3)

Equation at the end of step 2 :

(x + 1) • (x - 1) • (x + 3) • (x - 3) = 0

Step 3 :

Theory - Roots of a product :

3.1 A product of several terms equals zero.

When a product of two or more terms equals zero, then at least one of the terms must be zero.

We shall now solve each term = 0 separately

In other words, we are going to solve as many equations as there are terms in the product

Any solution of term = 0 solves product = 0 as well.

Solving a Single Variable Equation :

3.2 Solve : x+1 = 0

Subtract 1 from both sides of the equation :

x = -1

Solving a Single Variable Equation :

3.3 Solve : x-1 = 0

Add 1 to both sides of the equation :

x = 1

Solving a Single Variable Equation :

3.4 Solve : x+3 = 0

Subtract 3 from both sides of the equation :

x = -3

Solving a Single Variable Equation :

3.5 Solve : x-3 = 0

Add 3 to both sides of the equation :

x = 3

Supplement : Solving Quadratic Equation Directly

Solving x4-10x2+9 = 0 directly

Earlier we factored this polynomial by splitting the middle term. let us now solve the equation by Completing The Square and by using the Quadratic Formula

Solving a Single Variable Equation :

Equations which are reducible to quadratic :

4.1 Solve x4-10x2+9 = 0

This equation is reducible to quadratic. What this means is that using a new variable, we can rewrite this equation as a quadratic equation Using w , such that w = x2 transforms the equation into :

w2-10w+9 = 0

Solving this new equation using the quadratic formula we get two real solutions :

9.0000 or 1.0000

Now that we know the value(s) of w , we can calculate x since x is √ w

Doing just this we discover that the solutions of

x4-10x2+9 = 0

are either :

x =√ 9.000 = 3.00000 or :

x =√ 9.000 = -3.00000 or :

x =√ 1.000 = 1.00000 or :

x =√ 1.000 = -1.00000

Four solutions were found :

x = 3

x = -3

x = 1

x = -1

Processing ends successfully

User Wackozacko
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.